ChemInform Abstract: Selective Reduction of Amides to Amines by Boronic Acid Catalyzed Hydrosilylation. Issue 13 (1st April 2014) - Li, Yuehui; Molina de La Torre, Jesus A.; Grabow, Kathleen; Bentrup, Ursula; Junge, Kathrin; Zhou, Shaolin; Brueckner, Angelika; Beller, Matthias
Abstract A general method for the hydrogenative deoxygenation of tertiary, secondary, and primary amides into the corresponding amines is developed.